P11 QUICK PREVENTION OF THE POTENTIALLY SERIOUS CONSEQUENCES OF ELECTROMAGNETIC INTERFERENCE ON A ICD PATIENT THANKS TO THE REMOTE MONITORING SYSTEM OF THE DEVICE. (18th May 2022) - Fais, L; Floris, R; Angei, A; Farris, F; Frau, B; Giau, G; Racis, M; Delogu, G
Abstract: Clinical Case: We report the case of a 84–year–old female patient suffering from post–infarct heart disease with severe systolic dysfunction, wearing a dual–chamber defibrillator in secondary prevention because she had previously presented an episode of monomorphic ventricular tachycardia. After the implant, the patient was enrolled in the remote monitoring service of the device and constantly followed by our team. After a few months, at the remote control we found repeated episodes of very short duration of an alarm recognized by the device as ventricular arrhythmia in the VF window. Contrary to the arrhythmic interpretation of the device, the analysis of the EGM by the medical and nursing staff highlighted an electromagnetic interference defined by the type of signal, the presence of the same in all channels and by the lack of correlation with the underlying heart rhythm. The sensing of the ventricular lead was 5–6 mV, at the lower limits but stable over time, the other parameters were optimal. The patient was promptly contacted and questioned about the circumstances and symptoms: she was asymptomatic and we found that the interference came in conjunction with the use of a cordless telephone. The alarm was related to the electromagnetic field generated by the phone and the woman was asked to stop using the device with subsequent absence of device alarms. Electromagnetic interference in defibrillators can be a cause of potentially serious inappropriate therapies (ATP, pacing and shock), the analysis and correct interpretation of the EGM by the clinician is essential for the prevention of the same. Thanks to the efficiency of the remote monitoring service, the risk of serious consequences for our patient was avoided. Subsequently the lead was repositioned due to a worsening of the sensing, but even before the re–intervention there was no longer any false alarm thanks to the absence of the environmental source of interference. The remote monitoring service applied to implantable defibrillation systems is a valuable tool for identifying lead problems or, as in this case, environmental problems, and toprevent, thanks to rapid intervention, further potentially serious complications.